Prevalence and determinants of depression among patients with hypertension: A cross‑sectional comparison study in Ghana and Nigeria (2020)
Background: Despite evidence linking depression to poor blood pressure (BP) control and increased hypertension‑related morbidity and mortality, there is paucity of data about depression among patients with hypertension in sub‑Saharan Africa. We assessed factors associated with depression among patients with hypertension in Ghana and Nigeria. Subjects and Methods: Patients with hypertension were recruited from four hospitals: In Ghana, Korle Bu Teaching Hospital (n = 120), and in Nigeria, the University of Port Harcourt Teaching Hospital, the Lagos State General Hospital, and the University College Hospital Ibadan (n = 237). Demographic, socioeconomic, psychosocial, and clinical factors which predicted depression among the study cohort were assessed by logistic regression. Depression and beliefs about medications were assessed with the Patient Health Questionnaire (PHQ‑9) and the Beliefs about Medication Questionnaire, respectively. Depression was regarded as PHQ‑9 score >4. Results: The mean ages of the Ghanaian and Nigerian cohort were 57.0 ± 13.7 years (58.3% female) and 56.4 ± 12.9 years (57.0% female), respectively. Prevalence of depression was 41.7% and 26.6% among the Ghanaian and Nigerian cohorts, respectively. Significant predictors of depression in the Nigerian cohort were age in years [OR 0.97 (0.95–0.99)], concern about medications [OR 1.15 (1.03–1.30)], and poor BP control [OR 2.06 (1.09–3.88)]. Young age was the only independent predictor of depression in the Nigerian cohort. In the Ghanaian cohort, none of the factors significantly predicted depression. Conclusion: Prevalence of depression is high among patients with hypertension in Ghana and Nigeria. Screening and treatment of depression among patients with hypertension in Ghana and Nigeria may have important implications for improving outcomes.